The Allure of Easy Money: Sports Betting as a Coping Mechanism for Economic Hardship Among Tanzanian Youth: A Case Study of Dar es Salaam (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This study examines the proliferation of sports betting among youth in Dar es Salaam, Tanzania, as a response to persistent economic hardship and limited formal employment opportunities. Despite contributing over TZS 17.42 billion in taxes and generating substantial government revenue, Tanzania’s rapidly expanding betting industry has raised significant public health concerns, particularly among unemployed and underemployed young men who increasingly view gambling as a viable income generation strategy rather than entertainment. Drawing on qualitative case study methodology, this research explores how economic precarity shapes betting behaviors and why youth in Dar es Salaam turn to gambling as a perceived pathway out of poverty. Data from semistructured interviews with affected youth, family members, and mental health professionals reveal that betting companies strategically leverage success narratives and digital marketing to exploit economic vulnerabilities. The study also analyzes gaps in Tanzania’s current regulatory framework under the Gaming Act (CAP. 41) and draws comparative insights from effective interventions implemented in other emerging markets. Findings suggest that the normalization of betting as an economic coping mechanism reflects deeper structural failures in addressing youth unemployment and economic inclusion. This research contributes to the growing literature on gambling behaviors in low income settings and offers practical policy recommendations for balancing industry regulation with public health protection. The study underscores the urgent need for comprehensive interventions that address both the supply side of gambling services and the underlying economic drivers that make betting appealing to vulnerable populations.